Applying Systems Thinking to Education: The RISE Systems Framework - Spivack, Marla (Research on Improving Systems of Education (RISE), 2021)
Many education systems in low- and middle-income countries are experie ncing a learning crisis. Many efforts to address this crisis do not ac count for the system features of education, meaning that they fail to consider the ways that interactions and feedback loops produce outcome s. Thinking through the feedback relationships that produce the educat ion system can be challenging. The RISE Education Systems Framework, w hich is sufficiently structured to give boundaries to the analysis but sufficiently flexible to be adapted to multiple scenarios, can be hel pful. The RISE Framework identifies four key relationships in an educa tion system: politics, compact, management, and voice and choice; and five features that can be used to describe these relationships: delega tion, finance, information, support, and motivation. This Framework ca n be a useful approach for characterising the key actors and interacti ons in the education system, thinking through how these interactions p roduce systems outcomes, and identifying ways to intervene that can sh ift the system towards better outcomes.